Adherence of paediatric nurses to double checking process steps during medication administration in a children's hospital: an observational study. Issue 6 (9th May 2013) - Alsulami, Z; Choonara, I; Conroy, S
Abstract : Background: Medication errors have been reported to occur in 19.1% drug administration in children. 1 Double checking has been recommended to reduce medication errors in children. 2 There is insufficient evidence to either support or refute the practice of double checking the administration of medicines, 3 yet many hospitals use the process for drug administration in children. 4 Aims: To evaluate how closely double checking policies are followed by nurses in paediatric areas. Also, to identify the types, frequency and rates of medication administration errors that occurred despite double checking. Methods: This was a prospective observational study of paediatric nurses during double checking of medication administration in four wards in a 78 bed children's teaching hospital from April to July 2012. The observer followed the nurses during scheduled drug rounds (during week days and weekends) in each ward to observe and evaluate their adherence to the double checking procedure during the medication administration process. All data collected was anonymous and was recorded on a data collection form which was designed specifically for this study. Drugs were classified according to the BNF-C. The project was classed as service evaluation by the National Research Ethics Service and Trust clinical governance procedures were followed. Results: During a period of 11 weeks, 2000 drug dose administration events were observed in 876 paediatric patients. Oral drugs (84.7%) were administered and observed more frequently than other dosage forms. Non-opioid analgesic drugs were the most frequent group of medications administered (36%), followed by non-steroidal anti-inflammatory drugs (25%) and antibacterial drugs (24%). There was great variation between paediatric nurses in adherence to double checking steps during the medication administration process. Drug dose calculation was only double checked independently in 591 (29.5%) drug dose events, saline flush syringes were labelled and double checked in only 203 (67.2%) of 302 intravenous drugs. Intravenous bolus administration at the correct rate was double checked in only 213 (70.5%) of 302 intravenous drugs. Drug administration by two nurses at the bedside was observed in 1667 (83%) drug dose administrations. 128 medication administration errors were observed, an error rate of 6.4%. In addition, in 64 cases drugs were left for parents to administer without nurse's observation. Wrong administration technique errors (40%) was the most common type detected (eg, amoxicillin administered within 3 min instead of 5 min as prescribed) followed by incorrect preparation errors (35%) (eg, saline flush syringes prepared without label), and wrong time of administration errors (25%) (eg, ceftriaxone IV 2 h late). Conclusions: There was a variation between paediatric nurses adherence to double checking steps during medication administration. Independent double checks were not apparent for all steps in practice. The majority of medication administration errors observed failed to be prevented by the double checking process.